Biomedical coatings on magnesium alloys - a review - Hornberger, Helga; Virtanen, Sannakaisa; Boccaccini, Aldo R. (Acta Biomaterialia, 2012)
This review comprehensively covers research carried out in the field of degradable coatings on Mg and Mg alloys for biomedical applications. Several coating methods are discussed, which can be divided, based on the specific processing techniques used, into conversion and deposition coatings. The literature review revealed that in most cases coatings increase the corrosion resistance of Mg and Mg alloys. The critical factors determining coating performance, such as corrosion rate, surface chemistry, adhesion and coating morphology, are identified and discussed. The analysis of the literature showed that many studies have focused on calcium phosphate coatings produced either using conversion or deposition methods which were developed for orthopaedic applications. However, the control of phases and the formation of cracks still appear unsatisfactory. More research and development is needed in the case of biodegradable organic based coatings to generate reproducible and relevant data. In addition to biocompatibility, the mechanical properties of the coatings are also relevant, and the development of appropriate methods to study the corrosion process in detail and in the long term remains an important area of research. © 2012 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2012.tech.IW.LM.biomed
Keywords: Biodegradable materials; Coatings; Conversion; Deposition; Magnesium alloy